Self-Control Mediates, and Mobile Phone Dependence Moderates, the Relationship Between Psychological Capital and Attitudes Toward Physical Exercise Among Chinese University Students - Liu, Min; Li, Xinnan; He, Zhonghui (Frontiers in Psychology, 2022)
Physical exercise can improve the psychological capital while the attitude towards physical exercise will affect one's exercise behavior. However, moderating factors that may influence how physical exercise affects psychological capital remains unknown. We conducted a survey of 519 Chinese university students to investigate the mediating role of self-control between attitudes towards physical exercise and psychological capital, and whether this mediating role is moderated by mobile phone dependence. We found that attitudes towards physical exercise had a positive predictive effect on the psychological capital of university students. Besides, self-control mediated the relationship between attitudes towards physical exercise and psychological capital. The influence of self-control on psychological capital was moderated by mobile phone dependence: the influence of self-control on psychological capital decreased with higher mobile phone dependence. Our results suggest that attitudes towards physical exercise can positively predict the psychological capital of university students, with self-control playing a mediating role between them.